Pemetaan Geohazard Banjir Lahar Pada Daerah Aliran Sungai Batang Malano, Gunung Marapi, Sumatera Barat - Setiawan, Budhi; Nardi, Rajhi Febri (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
Geohazard Mapping of Lahar Floods in the Batang Malano River Basin, Mount Marapi, West Sumatra Periodic volcanic activity at Mount Marapi from January to March 2024 resulted in the accumulation of volcanic material around the crater and on the slopes. Increased rainfall triggered landslides, which carried this material into rivers and caused cold lava floods in May 2024. This study applied the Normalized Morphometric Flood Index (NMFI) method, which normalizes seven morphometric parameters—drainage density, bifurcation ratio, ruggedness number, slope, dissection index, basin relief, and relief ratio—on a scale of 0 to 1. These were classified into three hazard levels: low (36.89%), medium (60.59%), and high (2.52%). The Batang Malano watershed shows high vulnerability upstream, decreasing to moderate downstream. Given Mount Marapi’s continued eruptions into 2025, the risk of future lava floods remains significant. Strategic mitigation planning, evacuation routes, and resilient infrastructure are urgently needed along the Batang Malano watershed.